Controllability of quasilinear stochastic evolution equations in Hilbert spaces. (2001) - Balasubramaniam, P.
Abstract : Controllability of the quasilinear stochastic evolution equation is studied using semigroup theory and a stochastic version of the well known fixed point theorem. An application to stochastic partial differential equations is given.